2023
DOI: 10.3390/ijerph20031751
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Interocular Differences and Alcohol Consumption on Binocular Visual Performance

Abstract: The purpose of this study was to assess the influence of a moderate breath–alcohol content (BrAC of 0.40 mg/L) on binocular visual performance for different visual functions after inducing different levels of interocular differences with the use of filters. A total of 26 healthy young subjects were enrolled. The participants participated in two sessions: one without alcohol consumption and another after alcohol consumption. In each session and for the different filter conditions (subjects were wearing Bangerte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 89 publications
(147 reference statements)
2
2
0
Order By: Relevance
“…We found that visual impairment due to alcohol consumption could be expected to affect both eyes equally, the interocular differences being maintained before and after alcohol consumption. In a previous study 18 , we showed similar results taking into account the same ocular parameters and alcohol consumption condition where interocular differences significantly increased due to visual deterioration filters (BPM2 and BF_0.8 on the dominant eye). The two ocular parameters were considered due to their importance for quantifying intraocular scattering and straylight.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…We found that visual impairment due to alcohol consumption could be expected to affect both eyes equally, the interocular differences being maintained before and after alcohol consumption. In a previous study 18 , we showed similar results taking into account the same ocular parameters and alcohol consumption condition where interocular differences significantly increased due to visual deterioration filters (BPM2 and BF_0.8 on the dominant eye). The two ocular parameters were considered due to their importance for quantifying intraocular scattering and straylight.…”
Section: Discussionsupporting
confidence: 79%
“…We confirmed a correlation between visual performance in visual function and interocular differences in ocular parameters (ρ = − 0.370, p < 0.001), such that the greater the interocular differences in the ocular parameters studied, the poorer the visual performance. In a recent study 18 , we also found a correlation (ρ = − 0.390) between the overall binocular summation of several visual functions (VA, CS, and VDI) and interocular differences (including intraocular scattering, retinal-image quality, and straylight) when considering the same filter conditions and alcohol consumption. In contrast to that study, we have included stereopsis, which, as is well established, is an essential aspect of binocular vision and, therefore, visual performance.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…To clarify, stereopsis is a complex visual function that allows individuals to perceive the world in three dimensions, resulting from the brain's ability to integrate different images from each eye into a single, depth-laden visual field [1]. Stated differently, stereopsis refers to the visual ability to perceive depth by integrating two slightly different images from each eye into a single, three-dimensional representation [2].…”
Section: Introductionmentioning
confidence: 99%